Criminological Study Of Murder Crimes In Medan City - Yasmirah Mandasari Saragih; Rahul Ardian Fikri; Nabilah Syaharani (Res Judicata Law Review, 2024)
The actions of mugging and thuggery in the city of Medan are increasingly rampant and disturbing the community, they act without knowing the time and place , uniquely not adults but minors. A number of efforts have been made by the Mayor of Medan, Mr. Bobby Nasution to overcome the mugging and thuggery. In addition to conducting joint patrols until early morning , then holding a gathering with the TNI, Polri and the Motor Community in the city of Medan as an effort to maintain public order together . However, the program is less effective in eradicating mugging and thuggery in the city of Medan . In this study, the author will provide a criminological study of mugging crimes in the city of Medan. The discussion in this study is what factors cause children to commit mugging crimes in the city of Medan and how to reduce mugging crimes from a criminological study perspective. The type of research used in this study is empirical legal research, namely a legal research method that goes directly into the field. The results of the study are what factors cause children to commit mugging crimes, economic pressures and increasingly fierce urban survival patterns, which give rise to criminal acts. And efforts to reduce the crime of robbery by carrying out precision city patrol activities are carried out and implemented every day, both morning, afternoon and evening to suppress and reduce the space for perpetrators of criminal acts as a form of preventive police activity, which aims to reduce the number of criminal violations in the region.